The story of the SS Hitler's infamous legions of death - Cimino, Al (Arcturus Publishing Limited, 2018)
"The Schutzstaffel, or SS -- the brutal elite of the Nazi Party -- was founded by Hitler in 1925 to be his personal bodyguard. From 1929, it was headed by Heinrich Himmler, who built its numbers up from under 300 to well over a million by 1945. The SS became the very backbone of Nazi Germany, taking over almost every function of state. SS members were chosen not only to be the living embodiment of Hitler's notion of 'Aryan supremacy,' by also to cement undying loyalty to the Führer at every level of German society. Merciless fanatics in jackboots, the SS systematically slaughtered, tortured, and enslaved millions. This is the story of the rise and fall of one of the most evil organization the world has ever seen"--Back cover.